2023
DOI: 10.1007/s00432-023-04905-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a population-based breast cancer screening in North China

Abstract: Background Despite mammography-based screening for breast cancer has been conducted in many countries, there are still little data on participation and diagnostic yield in population-based breast cancer screening in China. Methods We enrolled 151,973 eligible women from four cities in Hebei Province within the period 2013–2021 and followed up until December 31, 2021. Participants aged 40–74 who assessed as high risk were invited to undergo breast ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…This might be explained by the fact that women who are concerned about their physical appearance and health are more likely to engage in physical activity. Previous research has found a link between mammography utilization and smoking status [67,68]. We found that the odds of adherence decreased 18% among women who were current smokers.…”
Section: Main Findingsmentioning
confidence: 49%
“…This might be explained by the fact that women who are concerned about their physical appearance and health are more likely to engage in physical activity. Previous research has found a link between mammography utilization and smoking status [67,68]. We found that the odds of adherence decreased 18% among women who were current smokers.…”
Section: Main Findingsmentioning
confidence: 49%